e-Rural: ambiente web para geração de conteúdos considerando a cultura e o nível de letramento do aprendiz - Magalhães, Vanessa Maia Aguiar de (2011)
This paper describes the process of developing and prototyping environment high-fidelity to develop culturally contextualized hyperdocuments web, adapted and made available according to the level of literacy of the learner, so it has access to and can understand the information and technological knowledge allowing your individual improvement and professional in the area it serves. This work focuses on health education, adopting the promotion of inclusive learning and continuous approaches using IHC, considering the literacy levels of learners, providing simplified lexical and syntactic processing and analogies based on common sense knowledge as an expression of the cultural context of the learner. The generation of hyperdocuments intended primarily for users involved in the Brazilian production of milk having difficulties in reading and access to technical information, presenting different levels of literacy and cultural profiles. To provide this inclusive and culturally diverse environment, firstly, there is a need for hyperdocuments are produced through translation of vocabularies and the identification of meanings, adapting them to the cognitive and linguistic needs of users, to assist them in understanding the training content and meaning. It is noteworthy that these hyperdocuments be adapted and made available according to the level of literacy of users, helping them to overcome cultural barriers, social, emotional, perceptual, and cognitive technology that impede their access to knowledge. For this it is necessary that these contents are to be made available providing text equivalents that replace or supplement the textual contents of the hypermedia, whether through images, videos, narration, text, or audio. In order to observe the process of development of computing and its functional prototype, collecting the views of the target audience and partners, were conducted feasibility studies and experiments with specialist area of computing and agribusiness research, reported in this paper, to verify the feasibility and applicability of the proposal in a real scenario. As a result, it is hoped that researchers and agricultural technicians to create content in context for many producers with different levels of literacy, and they can get an understanding of digital technical knowledge available, and therefore incorporates the technologies offered to improve the quality and productivity milk and other foods in your day-to-day.